An integrated adoption model for mobile services. (25th July 2012) - Lee, Sangjae; Noh, Mi–Jin; Kim, Byung Gon
This paper presents an integrated model for mobile services adoption using perceived usefulness, ease of use and enjoyment, and three groups of external factors, namely, service–related factors, user–related factors and technology–related factors, that affect perceived usefulness. An e–mail survey of 777 users and the analysis of a structural equation model support the research model in explaining the integrated aspects of adoption by examining the factors affecting intention to use mobile services. Differential effects of perceived enjoyment exist for services adoption among information, transaction and entertainment services. This suggests that service providers should align system functionality with service requirements for enjoyment.